Proceedings IEEE 56th Vehicular Technology Conference
DOI: 10.1109/vetecf.2002.1040755
|View full text |Cite
|
Sign up to set email alerts
|

Mobility/traffic adaptive location management

Abstract: This paper proposes "Mobility/Traffic Adaptive Location Management" that dynamically assigns the Location Area (LA) in response to each terminal's mobility and traffic characteristics to reduce the location management signals over the air. The optimum LA size depends on each mobile terminal's characteristics. The terminal velocity and call arrival rate are very important factors to determine the optimum LA size. The terminal velocity is measured in the mobile terminal by using GPS (Global Positioning System). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Previous research work on user-tracking mechanisms in cellular networks can be found in the literature [4]- [8]. However, most of these proposals address the issue of location management strictly as an optimization problem and, in general, do not consider the impact of their implementations in commercial networks (e.g., peaks of spurious signaling traffic may flood the network during global Tracking Area reconfigurations).…”
Section: Related Workmentioning
confidence: 99%
“…Previous research work on user-tracking mechanisms in cellular networks can be found in the literature [4]- [8]. However, most of these proposals address the issue of location management strictly as an optimization problem and, in general, do not consider the impact of their implementations in commercial networks (e.g., peaks of spurious signaling traffic may flood the network during global Tracking Area reconfigurations).…”
Section: Related Workmentioning
confidence: 99%
“…For the analysis that follows, we assume that the user moves randomly and that all the location areas under study have the same area, even if this size might not be optimum (dynamic location area size strategies are proposed in [30][31][32][33][34][35]). Under these assumptions, the frequency of the location updates depends on the speed of the mobile user, v, and the surface and perimeter length of the location areas.…”
Section: Background Information For the Analysis Of Location Update Cmentioning
confidence: 99%
“…Assuming that a user of a mobile communications network follows a random movement and that all the location areas under study have the same area, the frequency of the location updates will depend on the speed of the mobile user [19][20][21][22][23][24][25][26], v, and the surface and perimeter length of the location areas [27][28][29][30][31][32]. Taking into account that the location update operations can take place within a same VLR (case 1, with probability 1 β ), or between two VLRs, making use of the…”
Section: Calculation Of Location Update Costsmentioning
confidence: 99%